Self-compacting concrete using molybdenum mineral tailings: materials and mechanical property - Jae-Gwon Jeong; Joon-Yeong Kim; Jang-Un Kim; Minkwan Ju; Jiann-Wen Woody Ju (Discover Civil Engineering)
Abstract Recycling mineral tailings poses significant challenges, but one effective solution is their incorporation into self-compacting concrete (SCC) mixtures. This research explores the material and mechanical properties of SCC by integrating mineral tailings at three different ratios: 10%, 20%, and 30%. The primary aim is to determine the optimal replacement ratio that preserves key characteristics such as flowability and viscosity. To assess the material properties of fresh SCC, we conduct various tests, including rheological, V-funnel, U-box, and air content tests. These evaluations focus on how the addition of mineral tailings at different levels impacts flowability and viscosity. In terms of mechanical performance, we analyze compressive strength relative to the increasing proportion of mineral tailings. The results indicate that higher proportions of mineral tailings negatively affect flowability and viscosity. As a result, the optimal replacement ratio for mineral tailings is identified as up to 20% of the total cement content. These findings suggest that mineral tailings can effectively replace conventional cement, making them a promising option for producing environmentally friendly self-compacting concrete.